Learning and academic success in engineering courses: Comparing 1st year students according to gender - Vasconcelos, Rosa (2018)
This work in-progress research to practice paper analyzes the learning achievements of first-year engineering students, in order to observe if there are eventual gender differences. Studies suggest that women have higher enrollment rates and achievements in Higher Education. Women also dedicate more time studying and are more committed attaining their degree than men. Although the percentage of female students’ application in Science, Technology, Engineering and Mathematics (STEM) courses increased in the last years, there is still a greater proportion of women choosing higher education in social sciences and humanities areas. A sample of 723 1st year engineering students (66.8% male) was analyzed according to their academic background, their social origin and their habits of study. The results do not differentiate the Engineering Students according to their gender in socio-cultural variables of origin, however they significantly differentiate the two groups of students in their habits of study. Female students show greater organization of their time and activities of study, being also more thoughtful and self-regulated learners. At the same time, at the end of the first semester, they present a higher rate of successful curricular units and higher average grades. Some implications are highlighted for the teaching-learning process in engineering courses.